Sodium valproate-induced nocturnal enuresis in epilepsy: Three case reports and a review of the literature - Zhang, Xiaorong; Lu, Wei; Mo, Xiaoye (Frontiers in Neurology, 2023)
Background: Enuresis is an uncommon adverse effect of sodium valproate therapy that is unknown to most clinicians. This study provides an overview of the literature on enuresis associated with sodium valproate therapy, discussing the clinical manifestations and possible mechanisms of this side effect. Methods: We reported three cases of enuresis induced by sodium valproate and reviewed the published enuresis cases associated with sodium valproate therapy retrieved from databases. Case presentation and Results: Three new epileptic patients who presented with enuresis following sodium valproate therapy were reported, and 55 published cases of nocturnal enuresis associated with sodium valproate were evaluated. The average age of these patients varied from 4 to 20 years. Forty-eight of the cases had generalized seizures, 7 had focal seizures, and 3 had unknown seizures. In all the patients, the plasma concentration of sodium valproate was 80.76±14.80 μg/mL, within the therapeutic range when enuresis occurred. With discontinuation or reduction of the drug, all the patients recovered completely. Conclusions: Sodium valproate-induced enuresis is a rare and reversible side effect, characterized by occurring at a younger age, generalized onset of seizures, and a rather high dose. The possible mechanisms include insufficient secretion of anti-diuretic hormones, sleep disorder, and hyperactivity of the parasympathetic system. Clinicians should be aware of this uncommon side effect to avoid an incorrect adjustment of the treatment direction.